Structure Design Reveals the Role of Au for ORR Catalytic Performance Optimization in PtCo‐Based Catalysts. (6th April 2020) - Guo, Li‐Ming; Zhang, Dong‐Feng; Guo, Lin
Abstract: Au‐incorporation is a promising strategy to retard composition‐loss in Pt‐based catalyst. However, the unclear mechanism limits guided catalyst design and the performance optimization. Here, direct evidence is provided to validate the outward diffusion of Au atoms in Au‐core/Pt‐based‐shell structures. A Co interlayer is built between the Au‐core and PtCo‐based shell to exclude the possibility of atomic diffusion caused by interfacial alloying. In conjunction with the improved catalytic durability of the Au‐core@Pt‐based‐shell structure, it is reasonable to conclude that it is the subsurface segregated Au atoms rather than interfacial interaction that boosts the catalytic durability of Au‐core/Pt‐based‐shell structured catalysts towards oxygen reduction reaction. More importantly, by constructing Au‐core@Co‐interlayer@PtCoAu‐shell multilayer structure, the specific (1.730 mA cm −2 ) and mass (0.692 A mg −1 Pt ) activities are enhanced 7‐ and 4‐ fold relative to the commercial Pt/C. After 10 000 cycles of accelerated durability test, the mass activity loss for the multilayered catalyst is as low as 6.14% while the loss exceeds 35% for the commercial Pt/C catalyst. The improved catalytic performance of the Au@Co@PtCoAu multilayer structure can be ascribed to the finely modulated electronic structure and the compensated composition loss owing to the delicate structure and composition profile design. Abstract : PtAuCo‐shell‐based structures are achieved either by growth PtCo on Au nanoparticles or on Au@Co core–shell structures, demonstrating the outward segregation behavior of Au. The incorporation of Au improves the catalytic durability towards oxygen reduction reaction. The composition distribution profile illustrates that it is the subsurface segregated Au atoms rather than interfacial interaction boosts the catalytic durability of Au‐core/Pt‐based‐shell structures.